Effect of Carbohydrate Loading on the Well-Being of Patients Undergoing Elective Surgery - Enyedi MD PhD, Attila; Takács MD PhD, István; Győry MD PhD, Ferenc; Váradi MD, Csongor; Kóder MD, Gergely; Mudriczki MD, Gábor; Végh MD PhD, Tamás; Szamos MD, Katalin; Nádasi MD PhD, Edit; Szőllőssy-Csoma MD, Bálint; et al. (International Journal of Innovative Research in Medical Science, 2022)
Elective surgery is one of the main treatment modalities in modern medicine. Approximately 5% of the population undergo elective surgery each year. Traditional preoperative management calls for patients being fasted from midnight of the evening prior to surgery in order to decrease the risk of aspiration. For many years, this practice has been enforced, but over the past decades the scientific basis for fasting has been challenged. Perioperative fasting and surgical trauma contribute to increased postoperative morbidity and length of hospital stay. Preoperative oral carbohydrate loading recommended by the European Society of Anaesthesiology (ESA), Enhanced Recovery After Surgery (ERAS) and European Society for Clinical Nutrition and Metabolism (ESPEN) guidelines has been shown to reduce the development of insulin resistance by approximately 50% on the day after surgery. Moreover, it significantly reduces perioperative discomfort such as hunger, thirst, tiredness, weakness, and inability to concentrate. This clinical trial aimed to determine the efficacy and safety of a food for special medical purposes (FSMP) versus standard dietary management (fasting) in patients scheduled for elective surgery. The study was designed as a randomized, controlled, open-label, single centre clinical trial with an intervention (n=25) and a control group (n=25). Patients ages 18 years and older who were scheduled for elective surgery and required to fast the night and morning prior to surgery were enrolled into the study. The primary endpoint was thirst assessed during the morning of surgery. Secondary endpoints were assessed hunger, assessed feeling of agitation, feeling of fatigue, assessed feeling of weakness, and overall well-being. There was no significant difference (p=0.052) detected between the two groups when assessing thirst during the morning of surgery. There were significant differences between the two populations regarding hunger (p<0.001), feelings of agitation (p=0.012), feelings of fatigue (p<0.001) and overall well-being both before (p=0.001) and after surgery (p<0.001). No significant difference (p=0.398) was detected between the two populations regarding feelings of weakness. In our view, the use of the formula improves the well-being of patients. Our hypothesis is that the consumption of food for special medical purposes in the form of a transparent liquid containing only carbohydrates, instead of fasting before surgery, improves the well-being of patients. Our results suggest that MediDrink OpLoad can be an effective alternative to the standard dietary care of patients undergoing major surgery, and it can positively affect patient well-being.